Implementasi Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin (P5PPRA) pada Kurikulum Merdeka di Mis Ziyadatul Iman Kota Jambi - M. Alya Pratama Zulkarnaen; Ilyas Ilyas (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Abstract This study aims to investigate the implementation of the Project to Strengthen the Profile of Pancasila Students and Rahmatan lil Alamin Students (P5PPRA) within the Merdeka Curriculum for Grade 4 students at MI Ziyadatul Iman, Jambi City. The focus is on how the program is carried out and the factors that influence its success. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation. Data analysis involved data reduction, presentation, and conclusion drawing. The findings show that the implementation of P5PPRA consists of three key stages. First, the planning stage involves forming a facilitator team, assessing the school’s readiness, choosing project themes and dimensions, and preparing modules and schedules. Second, the implementation phase includes five steps: introduction, contextualization, action, reflection, and follow-up. Third, evaluation is conducted by teachers through performance assessments, evaluation of student products, and assessment of attitudes and skills, using both written tools and observation. Supporting factors include cooperation from school stakeholders, sufficient facilities, and available funding. Meanwhile, obstacles include a lack of teacher training on the Merdeka Curriculum and limited understanding of P5PPRA. By identifying these factors, schools can strengthen support and find solutions to challenges, helping ensure the program runs effectively.